Association of a vascular endothelial growth factor polymorphism with the development of bronchopulmonary dysplasia in Japanese premature newborns - Fujioka, Kazumichi (Nature Publishing Group, 2014)
Our objective was to correlate vascular endothelial growth factor (VEGF) genetic polymorphisms with the risk of bronchopulmonary dysplasia (BPD) development in premature newborns. Fifty-five newborns with BPD (BPD: median gestational age [GA]: 27 weeks, birthweight [BW]: 786 g) and 42 newborns without BPD (non-BPD: median GA: 29 weeks, BW: 1,165 g), who were born at <32 weeks gestational age and were admitted to Kobe University Hospital, were included. BPD was defined as oxygen dependency at 36 weeks postmenstrual age. Genomic DNA was extracted from the umbilical cord, cord blood, or buccal mucosa. Six VEGF genotypes (-1498T > C, -1154G > A, -634C > G, -7C > T, 936C > T, and 1612G > A) were determined by DNA sequencing. Clinical characteristics, and allele and genotype frequencies of VEGF in the BPD and non-BPD groups were analyzed. G allele frequencies in -634C > G of the BPD group were significantly higher than in the non-BPD group (66.4% vs. 50%, P = 0.02). -634C > G genotype distributions differed significantly between the BPD and non-BPD groups (BPD: CC 7%/CG 53%/GG 40%; non-BPD: CC 24%/CG 52%/GG 24%; P = 0.04). Multivariate logistic regression showed that duration of ventilation, VEGF-634G > C G alleles, and male gender were independent risk factors for BPD. In conclusion, polymorphism VEGF -634C > G may influence the risk of BPD.